2018
DOI: 10.1186/s12974-018-1367-2
|View full text |Cite
|
Sign up to set email alerts
|

Persistent reduction in sialylation of cerebral glycoproteins following postnatal inflammatory exposure

Abstract: BackgroundThe extension of sepsis encompassing the preterm newborn’s brain is often overlooked due to technical challenges in this highly vulnerable population, yet it leads to substantial long-term neurodevelopmental disabilities. In this study, we demonstrate how neonatal neuroinflammation following postnatal E. coli lipopolysaccharide (LPS) exposure in rat pups results in persistent reduction in sialylation of cerebral glycoproteins.MethodsMale Sprague-Dawley rat pups at postnatal day 3 (P3) were injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…Only a few in vitro studies have been performed so far; however, all of them consistently describe a decrease in sialylation in in ammation models 33,34 . This reduction in sialylation was also seen in an LPS-injected post-natal rat model 35 . Nonetheless, only perinatal infectious exposure was considered, and only one glycosylation trait was analysed (sialylation).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Only a few in vitro studies have been performed so far; however, all of them consistently describe a decrease in sialylation in in ammation models 33,34 . This reduction in sialylation was also seen in an LPS-injected post-natal rat model 35 . Nonetheless, only perinatal infectious exposure was considered, and only one glycosylation trait was analysed (sialylation).…”
Section: Introductionsupporting
confidence: 60%
“…It was seen that in all of these there were signi cant differences: a drastic decrease in sialylation (n=5, Paired Student's t-test, p<0. Sialylation and Fucosylation are the main traits dysregulated upon neuroin ammation General discrepancies in sialylation and fucosylation have been reported in CNS-impairments and neuroin ammatory scenarios 35,48 . Therefore, we looked further into these two features in the context of N-glycosylation (Figure 5).…”
Section: Lps-injected Striatum Displays Neuroin Ammatory Hallmarks Inmentioning
confidence: 99%
“…The glycosylation of IgGs and PBMCs was analyzed using biotinylated lectins in LB previously described (39). LB is also considered for quantitative analysis of glycosylation as described in previous studies (40,41). The lectin specificity was determined based on the glycoprotein reaction with lectins blocked by the inhibiting sugars or 200 mM acetic acid for 24h at 4°C.…”
Section: Lectin Blottingmentioning
confidence: 99%
“…It has been shown that postnatal inflammatory exposure causes ultimate increase in the activity of the neuraminidases NEU1 and NEU4. This increased neuraminidase activity immediately resulted in desialylation of glycoproteins of neural cells [ 130 ]. Furthermore, oxidative damage has been shown to desialylate cell surfaces [ 131 ].…”
Section: Effects Of Desialylation On Brain Innate Immunitymentioning
confidence: 99%